Surface-enhanced Raman spectroscopy (SERS) for detection of VX and HD in the gas phase using a hand-held Raman spectrometer. Issue 19 (27th July 2020) - Heleg-Shabtai, Vered; Sharabi, Hagai; Zaltsman, Amalia; Ron, Izhar; Pevzner, Alexander
Abstract : A sensitive surface-enhanced Raman spectroscopy (SERS) substrate was developed to enable hand-held Raman spectrometers to detect gas-phase VX and HD. Abstract : A sensitive surface-enhanced Raman spectroscopy (SERS) substrate was developed to enable hand-held Raman spectrometers to detect gas-phase VX and HD. The substrate comprised Au nanoparticles modified onto quartz fibres. Limits of detection (LOD) of 0.008 μg L −1 and 0.054 μg L −1 were achieved for VX and HD, respectively. Gas-phase experiments were performed using a homemade gas-phase flow system inside a climatic chamber at 25 °C and 50% relative humidity. Preliminary experiments were conducted using VX and HD in solution with Au and Ag nanoparticle colloidal suspensions. We developed and optimized several SERS methods for detection of VX and HD in solution. Gold nanoparticles were optimal for detection of VX and HD and were modified onto quartz fibres for gas-phase detection. The LODs for HD and VX detection in solution were 1.8 × 10 −3 μg mL −1 (1.1 × 10 −8 M) and 2.5 × 10 −3 μg mL −1 (9.3 × 10 −9 M), respectively. This study demonstrates that integration of SERS substrates with hand-held Raman spectrometers expands the applicability of Raman technology to homeland security, as reflected by increased sensitivity and gas-phase detection capabilities.